Effect of competence, discipline, and work stress on employee performance at PT Vayata Senada Cemerlang - Hendry Hendry; Wilson Wilson; Liyanti Liyanti; Walker Lee (Privietlab, 2023)
PT Vayata Senada Cemerlang it’s the company that does the selling building materials distri butor . and there are There are various factors that decrease performance, competence, discipline and job stress wan. Descriptive research explanatory which will carried out by and researchers compile questionnaires and use methods multiple regression. The conclusion is competence, discipline and work stress partially and simultaneously have a positive and significant effect on the performance of employees of PT Vayata Senada Cemerlang.